BLUE OCEAN STRATEGIES AT XYZ SAFARI RESORT'S HOTEL - Rustandi, Dedi (Dinasti International Journal of Economics, Finance & Accounting, 2020)
In the third quarter of 2018, growth in the hospitality sector by 4, 31% suffered a decline compared to growth in the third quarter of 2017 by 5, 58%. This is due to the increasingly intense competition in the digital era. Reported by the economics of Warta, economist from the Institute for Economic and Financial development, Bhima Yudhistira argues that the competition of hospitality business is becoming increasingly tight due to the increasing small hotels and Airbnb. Due to the increasingly competitive price, the hospitality business is hard to get too high profit. In the face of fairly tight competition, XYZ Safari Resort performs strategy analysis using the SWOT, TOWS, and Blue Ocean analysis methods, so that the appropriate strategy recommendation is achieved within the next period of time